ANALISIS KEMAMPUAN PENALARAN DAN ARGUMENTASI SISWA DALAM MENYELESAIKAN SOAL PISA DIKAJI BERDASARKAN GAYA BELAJAR - Danithania, Melsa; Hartoyo, Agung; Astuti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aimed to determine and describe the reasoning and argumentation abilities of students in solving PISA on change and relationship content studied based on learning styles in SMP Negeri 10 Pontianak. The research method use descriptive method with case studies. The subjects in this study were six students from all learning styles. The results of data analysis show that reasoning and argumentation abilities vary depending on their learning styles. Students who have a kinesthetic learning style have low reasoning and argumentation abilities in solving PISA because they are only able to achieve one of the three indicators perfectly. Students who have a visual learning style have reasoning and argumentation abilities in solving PISA quite well because they are able to achieve two of the three indicators perfectly. Students who have an auditory learning style have very low reasoning and argumentation abilities in solving PISA because they are unable to achieve all three indicators perfectly.Keywords: Reasoning and Argumentation Abilities, PISA, Learning Style